2017
DOI: 10.1016/j.bmc.2016.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and pharmacological evaluation of 4-hydroxyphenylglycine and 4-hydroxyphenylglycinol derivatives as GPR88 agonists

Abstract: The orphan receptor GPR88 is an attractive therapeutic target because of its implications in a number of basal ganglia-associated disorders. To date, pharmacological characterization of GPR88 has been limited due to the lack of potent and selective agonists and antagonists appropriate for CNS investigations. We have previously reported that GPR88 couples to Gαi proteins and modulates cAMP levels upon treatment with a small molecule agonist 2-PCCA. Recently, another chemotype of GPR88 agonist, represented by 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Such investigations would benefit both from the identification of putative endogenous ligands of GPR88 receptors and the availability of GPR88‐specific agonist and antagonists as pharmacological tools. However, despite reports on several promising agents like 2‐PCCA, RTI‐13951‐33, hydroxyphenylglycine and hydroxyphenylglycinol derivatives, no highly selective and brain‐penetrant agents suitable for clinical development have as yet been described 82‐86 . Moreover, selective antagonists are likewise eagerly awaited, although gene knockout and knockdown approaches have proven instructive for evaluating the function of GPR88 26,47,49 ; and antisense oligonucleotide strategies might be adopted for the regional neutralisation of GPR88 in disorders where it is thought to be overactive.…”
Section: Discussionmentioning
confidence: 99%
“…Such investigations would benefit both from the identification of putative endogenous ligands of GPR88 receptors and the availability of GPR88‐specific agonist and antagonists as pharmacological tools. However, despite reports on several promising agents like 2‐PCCA, RTI‐13951‐33, hydroxyphenylglycine and hydroxyphenylglycinol derivatives, no highly selective and brain‐penetrant agents suitable for clinical development have as yet been described 82‐86 . Moreover, selective antagonists are likewise eagerly awaited, although gene knockout and knockdown approaches have proven instructive for evaluating the function of GPR88 26,47,49 ; and antisense oligonucleotide strategies might be adopted for the regional neutralisation of GPR88 in disorders where it is thought to be overactive.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts in our laboratory have focused on the development of cAMP assays for the orphan GPR88 [14, 16, 18]. While the cAMP assay is a sensitive assay platform that measures GPR88 activation, using this platform for HTS has one major drawback.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the EC 50 values of (1 R ,2 R )-2-PCCA is possibly due to the sensitivity of the different assay systems. Another type of compound structurally related to 2-PCCA, represented by 2-AMPP [(2 S )- N -((1 R )-2-amino-1-(4-(2-methylpentyloxy)phenyl)ethyl)-2-phenylpropanamide], was also shown to activate GPR88 [17, 18]. Although (1 R ,2 R )-2-PCCA is useful in the characterization of in vitro signaling pathways of GPR88, it may not be as useful as an in vivo probe due to its high lipophilicity (cLogP 6.19) and reports that it is a P-glycoprotein substrate, both of which indicate that the compound is expected to have poor brain penetration [15].…”
Section: Introductionmentioning
confidence: 99%
“…Gpr88 is a neural orphan G protein-coupled receptor (GPCR) originally described as a striatal-enriched transcript (Mizushima et al 2000; Logue et al 2009; Ghate et al 2007; Massart et al 2009; Van Waes et al 2011) regulated by pharmacological treatment, including antidepressants (Conti et al 2007), mood stabilizers (Ogden et al 2004; Brandish et al 2005) or drugs of abuse (Le Merrer et al 2012; Befort et al 2008). Two synthetic agonists are proposed, Compound 19 not tested in vivo (Dzierba et al 2015) and 2-PCCA (Jin et al 2014; Bi 2013; Jin et al 2017) with unclear in vivo effects (Li et al 2013), hence our current knowledge of GPR88 function essentially stems from studies using mice lacking the Gpr88 gene ( Gpr88 -/- mice). Analyses of Gpr88 -/- mice have primarily focused on striatal function, and report altered dopamine signaling (Logue et al 2009), increased medium spiny neuron (MSN) excitability (Quintana et al 2012), altered locomotor responses to dopamine ligands (Quintana et al 2012) and amphetamine (Logue et al 2009) that was also observed upon local Gpr88 silencing in the rat ventral striatum (Ingallinesi et al 2015), reduced motor coordination and increased stereotypies (Meirsman et al 2016a; Quintana et al 2012).…”
Section: Introductionmentioning
confidence: 99%